Experimental studies of the nuclear-physical characteristics of the extended uranium target irradiated by relativistic protons, deutrons and ¹²C nuclei - Zhadan, A.A.; Sotnikov, V.V.; Voronko, V.A.; Baldin, A.A.; Tyutyunnikov, S.I.; Bukhal, O.V.; Husak, K.V.; Zhuk, I.V.; Zhivkov, P. (Вопросы атомной науки и техники, 2020)
In 2011-2017 in the framework of the international collaboration project “Energy and Transmutation of RAW”, a series of experimental studies on the deep subcritical uranium assembly QUINTA were carried out. The massive uranium target (512 kg of ⁿᵃᵗU) was irradiated with 0.66 GeV proton, deuterons and ¹²C nuclei (1 to 4 AGeV) from the Phasotron and Nuclotron accelerators (JINR, Dubna). The main results of experimental studies carried out with the participation of the Kharkov group of collaboration are presented. У 2011-2017 рр. у рамках Міжнародної колаборації «Енергія і трансмутація РАВ» було проведено серію експериментальних досліджень на глибоко підкритичній урановій збірці «КВІНТА». Масивна уранова мішень (512 кг ⁿᵃᵗU) збірки опромінювалася 0,66 ГеВ протонами, дейтронами і ядрами ¹²С (1…4 ГеВ/нукл.) від прискорювачів Фазотрон і Нуклотрон (ОІЯД, м. Дубна). Наведено основні результати експериментальних досліджень, які було виконано за участю харківської групи колаборації. В 2011-2017 гг. в рамках Международной коллаборации «Энергия и трансмутация РАО» была проведена серия экспериментальных исследований на глубоко подкритической урановой сборке «КВИНТА». Массивная урановая мишень (512 кг ⁿᵃᵗU) сборки облучалась 0,66 ГэВ протонами, дейтронами и ядрами ¹²С (1…4 ГэВ/нукл.) от ускорителей Фазотрон и Нуклотрон (ОИЯИ, г. Дубна). Представлены основные результаты экспериментальных исследований, выполненных при участии харьковской группы коллаборации.